Energy Security : Economics, Politics, Strategies, and Implications - Elkind, Jonathan; Pascual, Carlos, 1959- (Book collections on Project MUSE., 2010)
"This volume presents a realistic, cross-disciplinary look by recognized authorities at the global quest for energy security. While each nation faces different geopolitical, economic, and environmental challenges, the prescriptions offered here could well lead us in the right direction."--Jacket